Vectorized Treg-depleting αCTLA-4 elicits antigen cross-presentation and CD8+ T cell immunity to reject ‘cold’ tumors - Laetitia Fend; Eric Quemeneur; Monika Semmrich; Jean-Baptiste Marchand; Matilda Rehn; Nathalie Silvestre; Linda Mårtensson; Johann Foloppe; Ingrid Teige; Björn Frendeus; Petra Holmkvist; Carolin Svensson; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint blockade (ICB) is a clinically proven concept to treat cancer. Still, a majority of patients with cancer including those with poorly immune infiltrated ‘cold’ tumors are resistant to currently available ICB therapies. Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) is one of few clinically validated targets for ICB, but toxicities linked to efficacy in approved αCTLA-4 regimens have restricted their use and precluded full therapeutic dosing. At a mechanistic level, accumulating preclinical and clinical data indicate dual mechanisms for αCTLA-4; ICB and regulatory T cell (Treg) depletion are both thought to contribute efficacy and toxicity in available, systemic, αCTLA-4 regimens. Accordingly, strategies to deliver highly effective, yet safe αCTLA-4 therapies have been lacking. Here we assess and identify spatially restricted exposure to a novel strongly Treg-depleting, checkpoint-blocking, vectorized αCTLA-4, as a highly efficacious and potentially safe strategy to target CTLA-4.Methods A novel human IgG1 CTLA-4 antibody (4-E03) was identified using function-first screening for monoclonal antibodies (mAbs) and targets associated with superior Treg-depleting activity. A tumor-selective oncolytic vaccinia vector was then engineered to encode this novel, strongly Treg-depleting, checkpoint-blocking, αCTLA-4 antibody or a matching surrogate antibody, and Granulocyte-macrophage colony-stimulating factor (GM-CSF) (VVGM-αCTLA-4).Results The identified 4-E03 antibody showed significantly stronger Treg depletion, but equipotent checkpoint blockade, compared with clinically validated αCTLA-4 ipilimumab against CTLA-4-expressing Treg cells in a humanized mouse model in vivo. Intratumoral administration of VVGM-αCTLA-4 achieved tumor-restricted CTLA-4 receptor saturation and Treg depletion, which elicited antigen cross-presentation and stronger systemic expansion of tumor-specific CD8+ T cells and antitumor immunity compared with systemic αCTLA-4 antibody therapy. Efficacy correlated with FcγR-mediated intratumoral Treg depletion. Remarkably, in a clinically relevant mouse model resistant to systemic ICB, intratumoral VVGM-αCTLA-4 synergized with αPD-1 to reject cold tumors.Conclusion Our findings demonstrate in vivo proof of concept for spatial restriction of Treg depletion-optimized immune checkpoint blocking, vectorized αCTLA-4 as a highly effective and safe strategy to target CTLA-4. A clinical trial evaluating intratumoral VVGM-αhCTLA-4 (BT-001) alone and in combination with αPD-1 in metastatic or advanced solid tumors has commenced.